Association of Hypertension and Chronic Kidney Disease in Population Aged ≥18 Years Old - Rizka Ramadhanti; Helda Helda (Cell and BioPharmaceutical Institute, 2021)
Background: Chronic kidney disease (CKD) is a global public health problem, due to the increasing prevalence and incidence of kidney failure, poor prognosis, and required high costs for its treatment. Hypertension as the dominant risk factor for CKD also has a high prevalence which keep increasing in DKI Jakarta. This study aimed to determine the association between hypertension and the incidence of CKD in people aged ≥18 years old in DKI Jakarta Province.Materials and method: This was a quantitative research with an analytic cross-sectional study design. The data source used was secondary data obtained from Basic Health Research (Riset Kesehatan Dasar/Riskesdas) 2018. There were 7,141 samples that matched the inclusion and exclusion criteria.Results: The proportion of CKD and hypertension in people aged ≥18 years old in DKI Jakarta Province were 0.5% and 16.6%, respectively. There was a significant association between hypertension and CKD with a prevalence odds ratio (POR) of 3.140 (95% CI: 1.527-6.453) after being adjusted by the age variable. Several other characteristics such as age (POR = 3.912; 95% CI: 1.932-7.918), diabetes mellitus (POR = 3.412; 95% CI: 1.405-8.285), heart disease (POR = 7.323; 95% CI: 3.158- 16.982), and physical activity (POR = 2.324; 95% CI: 1.148-4.703) were also significantly associated with the incidence of CKD.Conclusion: Someone who has hypertension has 3.14 times (95% CI: 1.527-6.453; p-value = 0.002) chance of suffering from CKD compared to someone who does not have hypertension after being controlled by the confounding variable, age.Keywords: chronic kidney disease, hypertension, DKI Jakarta, Basic Health Research 2018